The interaction between cigarette smoking on the incidence of hypertension among adolescents - Hidayat, Tin Kumalasari; Herawati, Vitri Dyah; Suwarni, Anik (JOURNAL OF Mental Health Concerns, 2025)
Background: Hypertension is a non-communicable disease known as the "silent killer" because it often has no symptoms but can lead to serious complications such as stroke, heart failure, and kidney disease. The prevalence of hypertension in adolescents is increasing, and one contributing risk factor is smoking. Cigarettes contain harmful substances such as nicotine, tar, and carbon monoxide, which can damage the cardiovascular system and trigger increased blood pressure. Purpose: To determine the correlation between cigarette smokings and the incidence of hypertension in adolescents in Mojo Wetan Village at Sragen Regency. Method: A quantitative approach with a descriptive correlation and cross-sectional design. The population of this study was all male adolescents aged 15– 24 years who had a cigarette smoking in Mojo Wetan Village. The sample size was 39 respondents, selected using a total sampling technique. Data were collected using a cigarette smokings questionnaire and a calibrated needle sphygmomanometer. Data were analysed univariately and bivariately using Kendall's Tau test. Results: The majority of respondents had a moderate cigarette smoking (43.6%), and most were in the normal blood pressure category (59%). The Kendall's Tau test showed a significant association between cigarette smokings and the incidence of hypertension in adolescents (p-value = 0.002) with a correlation coefficient of 0.406. Conclusion: There is a significant correlation between cigarette smokings and the incidence of hypertension in adolescents in Mojo Wetan Village. The higher the cigarette smoking, the greater the likelihood of adolescents experiencing pre-hypertension or hypertension. Keywords: Adolescents; Hypertension; Cigarette Smoking.